Real-time deformability cytometry: Label-free functional characterization of cells - Herbig, Maik; Kraeter, Martin; Plak, Katarzyna; Mueller, Paul; Guck, Jochen; Otto, Oliver (Humana Press Inc., 2018)
Real-time deformability cytometry (RT-DC) is a microfluidic technique that allows to capture and evaluate morphology and rheology of up to 1000 cells/s in a constricted channel. The cells are deformed without mechanical contact by hydrodynamic forces and are quantified in real-time without the need of additional handling or staining procedures. Segmented pictures of the cells are stored and can be used for further analysis. RT-DC is sensitive to alterations of the cytoskeleton, which allows, e.g., to show differences in cell cycle phases, identify different subpopulations in whole blood and to study mechanical stiffening of cells entering a dormant state. The abundance of the obtainable parameters and the interpretation as mechanical readout is an analytical challenge that needs standardization. Here, we will provide guidelines for measuring and post-processing of RT-DC data.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Automated segmentation; Cell mechanics; Cytoskeleton; Image analysis; Label-free cytometry; Linear mixed models; Microfluidics; Morphometry; Rheology